Kuzey Kıbrıs Türk Cumhuriyeti`nde Okutulan Kıbrıs Tarihi Ders Kitaplarındaki “Tarih Öncesi Çağlar” Ünitelerinin İçerik Analizi / Content Analysis of Units on "Prehistoric Ages" of Cyprus History Course Books in Turkish Republic of Northern Cyprus - Özkul, Ali Efdal; Ülvay, Gülcan Faika (Journal of History Culture and Art Research, 2017)
Abstract This study is based on the content analysis of the units on pre-historic periods of Cyprus History, Book 1 used in secondary schools between 2004 and 2009 and of Turkish Cypriot History, 6th Grade Books used for the secondary schools between 2009 and 2016. Mixed research methods, which compromises qualitative and quantitative research method, was used in this study. The qualitative part of the study includes the examination of the units on prehistoric ages in the textbooks according to criteria such as concepts, skills and visuals. In the quantitative part of the study, it has been consulted 67 teachers who are able to give a history lesson in secondary schools. According to the findings obtained from the study, it is possible to say that the opinions of the teachers with regard to the Cyprus History, Book I between 2004-2009 are more positive than 6th Grade Books of Cyprus History between 2009-2016. Additionally, it was seen that there were missing points in the units on pre-historic periods of the said course books in terms of concepts, skills and visuals. Öz Çalışmada 2004-2009 yılları arasında orta dereceli okullarda okutulan Kıbrıs Tarihi 1. Kitap ile 2009-2016 yılları arasında orta dereceli okullarda okutulan Kıbrıs Türk Tarihi 6. Sınıf ders kitaplarının tarih öncesi devirlerini içeren ünitelerinin içerik açısından değerlendirilmesi esas alınmıştır. Çalışmada nitel ve nicel araştırma yöntemlerini içerisine alan karma araştırma modeli kullanılmıştır. Çalışmanın nitel bölümünde ders kitapları içerisinde yer alan tarih öncesi çağları içeren ünitelerin kavramlar, beceriler ve görseller gibi kriterler doğrultusunda incelenmesi yer almaktadır. Araştırmanın nicel bölümünde ise orta dereceli okullarda tarih dersi verebilecek niteliklere sahip 67 öğretmenin görüşüne başvurulmuştur. Çalışmanın sonucunda elde edilen bulgulara göre 2004-2009 Kıbrıs Tarihi 1. Kitap ders kitabına ait öğretmen görüşlerinin 2009-2016 Kıbrıs Türk Tarihi 6. Sınıf ders kitabı öğretmen görüşlerine göre daha olumlu olduğunu söylemek mümkündür. Ayrıca söz konusu ders kitaplarının tarih öncesi devirleri içeren ünitelerinde kavramlar, beceriler ve görseller açısından eksikliklerin yer aldığı görülmektedir.